Error Analysis in Language Teaching and Learning - Binaningrum, Banun (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
This paper tries to describe the function of error analysis in teaching and learning target/foreign languages. The term of target/foreign language here, refers to the language which is being learned by the students. While, the term of first language refers to the language which has been mastered earlier by the students, the first language here may also refer to the students’ mother tongue, although in the study of language acquisition the two terms should be differed clearly. This paper also tries to explain the relationship between error analysis and contrastive analysis. Both of the analyses are sometimes used in the teaching and learning of languages. Besides that, this article also presents the causes of errors made by the students, the impacts of the errors in communication, and the techniques to avoid, to reduce and to combat the errors in learning and teaching the target languages. Notes: In this paper there are some signs: * —indicates the part of error, — indicate the missing part that become an error. There are also symbols of phonetics derived from English Pronouncing Dictionary written by Daniel Jones.